John Fiske papers - Fiske, John, 1842-1901.
Letters concerning lectures, finances, travel, Fiske's literary and political ambitions, and other matters, written mainly to his mother, Mary Fiske (Bound) Green Stoughton, and his wife, Abby Morgan Fiske, during lecture tours and periods of study and travel in the U.S. and Europe.
Formerly part of the John Fiske papers now in the Henry E. Huntington Library.
Historian, philosopher, and librarian. Name originally Edmund Fiske Green; at age thirteen, took name of maternal great-grandfather, John Fiske.
Collection material in English.
Keywords: Literature; Fiske, Abby Morgan -- Correspondence; Stoughton, Mary Fisk Bound Green -- Correspondence; Europe -- Description and travel; United States -- Description and travel; Historians; Librarians; Philosophers